2013
DOI: 10.1155/2013/624245
|View full text |Cite
|
Sign up to set email alerts
|

From (Un)Willingness to InvolveMENt: Development of a Successful Study Brand for Recruitment of Diverse MSM to a Longitudinal HIV Research

Abstract: Background HIV continues to be a major concern among MSM, yet Black MSM have not been enrolled in HIV research studies in proportionate numbers to White MSM. We developed an HIV prevention research brand strategy for MSM. Methods Questionnaires and focus groups were conducted with 54 participants. Descriptive statistics and chi-square analyses were performed and qualitative data were transcribed and content analyzed to identify common themes. Results Formative research results indicated that younger Black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…consistent with similar school injury studies in the region namely, that 'Fall' injuries are the most common mechanism, particularly among boys of a young age [13][14][15][16][17][18][19][20][21][22].…”
Section: Plos Onesupporting
confidence: 86%
See 3 more Smart Citations
“…consistent with similar school injury studies in the region namely, that 'Fall' injuries are the most common mechanism, particularly among boys of a young age [13][14][15][16][17][18][19][20][21][22].…”
Section: Plos Onesupporting
confidence: 86%
“…Relative to other regional studies, this study estimated a school injury rate of 419/1000, which is comparable to rates suggested by Eastern Mediterranean countries, including Jordan (437/1000), Egypt (385/1000), Oman (263/1000), and UAE (307/1000) [13][14][15][16][17][18][19][20][21], retrieved from the Global School-Based Students Health Survey (GSBHS). Findings from this study are https://doi.org/10.1371/journal.pone.0233465.g001…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Ultimately, fatigued recipients are at risk of forgoing the advice of these health campaigns. Condom use has already been identified as one health guideline negatively impacted by message fatigue ( Frew et al, 2013 , So et al, 2017 ). The introduction of additional health guidelines likely risks accelerating fatigue.…”
Section: Introductionmentioning
confidence: 99%